Signal processing of airborne radar stations : plane flight control in difficult meteoconditions /: plane flight control in difficult meteoconditions. ([2020]) - Vereshchagin, A. V; Zatuchny, D. A; Sinitsyn, V. A; Sinitsyn, E. A; Shatrakov, Y. G
No abstract available